UPAYA PENCEGAHAN DAN PENANGAN STUNTING MELALUI EDUKASI DAN PENGOLAHAN PANGAN “PANTING” PATIN CEGAH STUNTING DI DESA TATAH BANGKAL - Aisyah, Noor; Riko Nugroho, Muhammad; Putri, Aisya Novrida; Norhalisa; Wandarie, Indah; Andriyani, Novita; Rahma Syari, Aulia; Lathifah, Nor; Dhiya Kamila, Marsa; Niah, Rakhmadhan (Jurnal Bakti untuk Negeri, 2025)
Stunting is a condition of toddlers with short stature, a chronic nutritional problem that usually occurs during the first 1000 days of life (HPK). Stunting is characterized by a toddler's length or height that is not in accordance with their age. The number of stunting in children under the age of five is more common in rural areas compared to urban areas, although in general the prevalence has decreased. This difference is caused by various complex factors, including socio-demographic aspects, economic disparities, and unequal access to health services. This activity aims to increase knowledge and processing of catfish nuggets for pregnant women and mothers whose children are indicated as stunting. The implementation method is carried out through education, socialization and distribution of leaflets related to stunting, processing of catfish nuggets and pre-test and post-test evaluations. The results of the activity showed an increase in participants obtained from 27 participants, namely ... before the presentation of the material to ... after the presentation. It is hoped that this activity will motivate participants to reduce stunting rates in Tatatah Village, Bangkal.